Notesannuities - x = 1 g 1 r to get PV = 1 1 r 1&& 1 g 1 r ± T 1& 1 g 1 r = 1&& 1 g 1 r ± T(1 r h 1& 1 g 1 r i = 1&& 1 g

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
1 Annuities and Perpetuities: The goal of these notes is to derive all perpetuity and annuity formulas. It turns out that we only need to know one calculus formula: T X j =1 x j 1 = 1 x T 1 x (1) The proof of this calculus formula is at the end of this document (for those should be really excited now! A growing annuity has the following cash ±ows: t = 0 t = 1 t = 2 t = 3 ... T 0 1 1 + g (1 + g ) 2 ... (1 + g ) T 1 (2) Then, we can conveniently write this as: (The P sign just indicates summation) PV = T X t =1 (1 + g ) t 1 (1 + r ) t (3) First trick: Multiply and divide by (1 + g ) : PV = T X t =1 (1 + g ) t 1 (1 + r ) t 1 + g 1 + g = 1 1 + g T X t =1 (1 + g ) t (1 + r ) t (4) = 1 1 + g T X t =1 1 + g 1 + r ± t Second trick: De²ne x ± 1+ g 1+ r so that: PV = 1 1 + g T X t =1 x t (5) We can almost use the formula in equation 1 (look at the exponent!!). Mr. Smart has another idea: Multiply and divide by x : PV = 1 1 + g T X t =1 x t x x (6) = x 1 + g T X t =1 x t 1 (7) 1
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Now we can apply formula 1 for the term: P T t =1 x t 1 = 1 x T 1 x and obtain: PV = x 1 + g 1 x T 1 x (8)
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x = 1+ g 1+ r to get: PV = 1 1 + r 1 & & 1+ g 1+ r ± T 1 & 1+ g 1+ r = 1 & & 1+ g 1+ r ± T (1 + r ) h 1 & 1+ g 1+ r i = 1 & & 1+ g 1+ r ± T 1 + r & (1 + g ) = 1 & & 1+ g 1+ r ± T r & g (9) That±s it!! From here, we can easily derive all formulas: T & period Annuity (no problem, set g = 0) 1 & ( 1 1+ r ) T r T & period growing annuinty (we solved for this!) 1 & ( 1+ g 1+ r ) T r & g Growing Perpetuity (let T ! 1 ), works only if g < r , why?? 1 r & g Regular Annuity 1 r Proof. T X j =1 x j & 1 = T & 1 X j =0 x j = ² 1 + x + x 2 + x T & 1 ³ Multiply both sides by (1 & x ) and you obtain: (1 & x ) T X j =1 x j & 1 = (1 & x ) ² 1 + x + x 2 + x T & 1 ³ = ² 1 + x + x 2 + x T & 1 ³ & x ² 1 + x + x 2 + x T & 1 ³ = ² 1 + x + x 2 + x T & 1 ³ & ² x + x 2 + ::: + x T ³ = 1 & x T Hence: (1 & x ) T X j =1 x j & 1 = 1 & x T or T X j =1 x j & 1 = 1 & x T 1 & x 2...
View Full Document

This note was uploaded on 10/02/2009 for the course UGBA 08547 taught by Professor Odean during the Fall '09 term at University of California, Berkeley.

Page1 / 2

Notesannuities - x = 1 g 1 r to get PV = 1 1 r 1&& 1 g 1 r ± T 1& 1 g 1 r = 1&& 1 g 1 r ± T(1 r h 1& 1 g 1 r i = 1&& 1 g

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online